Global, diffuse and direct solar radiation at the surface in the city of Rio de Janeiro: Observational characterization and empirical modeling - Marques Filho, Edson P.; Oliveira, Amauri P.; Vita, Willian A.; Mesquita, Francisco L.L.; Codato, Georgia; Escobedo, João F.; Cassol, Mariana; França, José Ricardo A. (Renewable energy, 2016)
The city of Rio de Janeiro and others 18 cities compose the Metropolitan Area of Rio de Janeiro. The main objective of this work is to characterize observationally the diurnal and seasonal evolution of the solar radiation components in the city of Rio de Janeiro. The measurements of global and diffuse solar radiation and standard meteorological variables at the surface have been carried out regularly at the Geoscience Institute of Federal University of Rio de Janeiro since October of 2011. The microclimatic conditions show that the period 2011–2014 was warmer during most of the year and drier in summer and spring in comparison with climate normal. All solar radiation components present a well defined diurnal cycle with maximum at noon. The estimates of global and direct solar radiation indicate a great potential available for solar energy at the surface, particularly in summer. The behavior of the clearness index and diffuse solar radiation fraction is similar in summer and winter. The Angstrom formula represents properly the estimate of the monthly average daily value of global solar radiation. The sigmoid logistic function is statistically more significant in comparison with others correlation models to represent the diffuse fraction as a function clearness index. •Observational characterization of the solar radiation components at surface.•Angstrom formula represents properly the monthly average of global solar radiation.•The sigmoid function is adequate to estimate the hourly diffuse fraction.